Development of nursing competencies and the role of medical simulation in nursing education - Kwilosz, Edyta; Badora-Musiał, Katarzyna; Petka-Nosal, Natalia; Kowalska-Bobko, Iwona; Gniadek, Agnieszka (Medical Studies/Studia Medyczne, 2026)
Dynamic demographic and epidemiological changes, together with increasing demands for healthcare quality, have driven the development of Advanced Practice Nursing (APN), characterized by expanded autonomy and advanced clinical competencies. Medical simulation plays an important role in preparing nurses for these responsibilities by integrating theoretical knowledge with practice, supporting decision-making and communication skills. This study aimed to analyze the development of nursing competencies in Poland within the European context and to evaluate the role of medical simulation in preparing nurses for APN roles. A narrative rapid review was conducted. Literature published between 2015 and 2026 was identified in PubMed, Scopus, CINAHL, and the Polish Medical Bibliography, along with selected national and international legal documents. Data were analyzed using narrative synthesis supported by thematic tables. Expanding nursing competencies enhances professional autonomy and professionalization but requires educational and legal reforms. Medical simulation supports competency implementation and improves patient care quality.